PENGARUH RESIKO FINANSIAL DAN RISIKO OPERASI TERHADAP BETA SAHAM SYARIAH DAN BETA SAHAM KONVENSIONAL (Studi pada Saham Manufaktur yang terdaftar dalam Bursa Efek Indonesia) - Wardani, Kingkin (Universitas Darrussalam Gontor, 2014)
The purpose of this research is to determine the differences of systematic risk and financial risk between Islamic shares and conventional shares are listed in Indonesia Stock Exchange (BEI). The second purpose is to determine the effect of financial risk and operating risk to beta of the Islamic shares and conventional shares listed in Indonesia Stock Exchange (BEI). This study uses two methods to test the research hypothesis. The first method is the difference test (independent t-test and Mann Whitney test) in order to examine average of systematic risk (beta) and the average financial risk between Islamic shares and conventional shares. The second method is multiple regression that used to determine the effect of financial risk and operating risk to the systematics risk (beta) of Islamic shares and conventional shares. The sample in this research are listed shares on the Indonesia Stock Exchange (BEI) in the manufacturing industry. Study sample amounted to 50 shares for one period (2008-2011). Fiftieth of the sample are eliminated because the data not eligible. After elimination of the number of observations become 151 observation. The results of this study indicate : (1) based on Independent t-test, the beta value of the Islamic shares not significantly smaller than conventional beta stocks. (2) Based on t-test show that financial risk have a positive effect and significant to the beta of Islamic shares and conventional shares, while the operating not affecting the beta of Islamic shares and conventional shares. (3) Based on Mann-Whitney test, the financial risk of Islamic share smaller and significant than the financial risk of a conventional shares.